(untitled) (Mustansiria Dental Journal, 2019)
Aim: the study was undertaken to assess the effect of various metal oxides on some mechanical properties of acrylic resin. Materials and methods: Two hundred acrylic specimens were constructed in total. There were two tests utilized (transverse and hardness). For each test, there were nine experimental groups according to the type of metal oxides used. The specimens without use any of metal oxides were considered as control. For transverse test, the specimens were exposed to loads until fracture. For hardness test, the specimens were tested; values were obtained. All data were analyzed and compared using ANOVA and tukey tests. Results: the addition of metal oxides at different concentrations enhanced the transverse strength of acrylic. Significant differences were statistically found between experimental groups and control group (P<0.001); among experimental groups (P<0.001). For hardness test, there was a slight increase in the mean values of hardness of clear acrylic as the concentration of metal oxides increases. No significant differences were statistically found among experimental groups (P>0.05); between experimental groups and control group (P>0.05) except there was significant difference between control and 5% TiO2 group (P<0.05). Conclusion:The incorporation of metal oxides improved the transverse strength and surface hardness of acrylic resin.